2010
DOI: 10.1039/c000076k
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, stable, tunable, and easy to synthesize, handle and recycle luminescent materials: [H2NMe2]3[Ln(iii)(2,6-dipicolinolate)3] (Ln = Eu, Tb, or its solid solutions)

Abstract: Three compounds with the general formulae [H(2)N(Me)(2)](3)[Ln(2,6-dpa)(3)] were prepared from cheap and readily available reactants. Microcrystalline compounds could be isolated in high yields (>80%) by a simple filtration, after only one hour reaction time in refluxing DMF. The Eu and Tb compounds have been structurally characterized by single crystal X-ray diffraction. The compounds have unusual high-absorption coefficients (>95%) and quantum efficiencies (approximately 70%). Furthermore, they are thermally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 57 publications
4
20
0
Order By: Relevance
“…A loss step with weight loss rate of 29.53 % arose in the range of 273-342°C, which was due to the skeleton fracture of the Dy(BA) 3 phen. It indicated that the Dy(BA) 3 phen had been partially decomposed which might be from the decomposition of free ligand BA 3 phen began to violent decomposition at 512°C taking off the BA and 1,10-phenanthroline with weight loss to 38.38 %. The DSC curves tended to be stabilizing when the temperature was close to 600°C.…”
Section: Thermal Properties Of Dy(lc) 3 Phenmentioning
confidence: 97%
See 3 more Smart Citations
“…A loss step with weight loss rate of 29.53 % arose in the range of 273-342°C, which was due to the skeleton fracture of the Dy(BA) 3 phen. It indicated that the Dy(BA) 3 phen had been partially decomposed which might be from the decomposition of free ligand BA 3 phen began to violent decomposition at 512°C taking off the BA and 1,10-phenanthroline with weight loss to 38.38 %. The DSC curves tended to be stabilizing when the temperature was close to 600°C.…”
Section: Thermal Properties Of Dy(lc) 3 Phenmentioning
confidence: 97%
“…The thermal decomposition processes of the Dy(Lc) 3 phen(Lc = AA, MAA, BA, SA) complexes are the similar. The thermal decomposition temperature of Dy(MAA) 3 phen, Dy(AA) 3 phen, Dy(BA) 3 phen and Dy 2 (SA) 3 phen 2 are about 261, 278, 273 and 216°C, respectively. The thermal decomposition temperature of Dy 2 (SA) 3 phen 2 was the lowest.…”
Section: Thermal Properties Of Dy(lc) 3 Phenmentioning
confidence: 99%
See 2 more Smart Citations
“…Dipicolinates are versatile N,O-chelating ligands with a large number of coordination modes varying from bidentate or tridentate chelating to bridging via one or more carboxylate oxygen atoms, capability to stabilize water clusters (Das and Baruah, 2013) and function as hydrogen-bond acceptors as well as hydrogen-bond donors (Sharif et al, 2012;Ucar et al, 2007). Moreover, dipicolinates in combination with metal aqua ions, which have high affinity towards the formation of strong H-bonds, may result into the formation of 2-D or 3-D H-bonded metaloorganic frameworks with diverse topologies and interesting properties (Kirillova et al, 2007 ) were spectroscopically and structurally investigated (Laine et al, 1995;Wang et al, 2004;Wen et al, 2002;Qi et al, 2004 II and m = 2-3) were characterized by IR and UV/Vis spectroscopy, elemental analysis and single-crystal X-ray diffraction analysis (Kirillova et al, 2008 (Sharif et al, 2012) and similar dipicolinate compounds with lanthanides (Brayshaw et al, 2005;Ghosh and Bharadwaj, 2004;Mooibroek et al, 2010;Reinhard and Güdel, 2002;), were also studied. Compounds of this type, due to their crystal structures and the resulting interesting properties, can find their applications in the fields of aqueous chemistry, catalysis, supramolecular medicinal chemistry (Yang et al, 2002), crystal engineering (Mirzaei et al, 2014;Pramanik & Das, 2009), bioinorganic chemistry, material chemistry and magnetic materials (Brayshaw et al, 2005;Parent et al, 2007) ) of cobalt(II) acetate tetrahydrate (for compound 1) or nickel(II) acetate tetrahydrate (for compound 2; both 0.25 g; 1.00 mmol), a stoichiometric amount of bathocuproine (0.36 g; 1.00 mmol) was added, the reaction mixture was stirred and heated for approximately 30 minutes and then treated with 2,6-pyridinedicarboxylic acid (dipicolinic acid; 0.17 g; 1.00 mmol) in the molar ratio of 1:1:1, heated to the boiling point and cooled down to the laboratory temperature.…”
Section: Introductionmentioning
confidence: 99%